Multi-level adaptive coordinated AC fault ride-through control strategy for hybrid cascaded UHVDC transmission system - LYU Yanbei; ZHAO Wenqiang; SHI Qiaoming; YAO Qixin; SUI Shunke; CHANG Haotian (电力工程技术)
Hybrid cascaded ultra high voltage direct current (UHVDC) integrates the advantages of line commutated converters (LCC) and voltage source converters (VSC). However, there is surplus power on the direct current (DC) side during alternating current (AC) faults at the receiving end, which may cause overvoltage issues in VSC sub-modules. Based on the topological features of the hybrid cascaded UHVDC system, a multi-level adaptive coordinated control strategy is proposed, utilizing operation modes and electrical signals. Multi-level control strategies, namely controlling the negative sequence voltage of the faulty VSC converter, adopting the auxiliary DC voltage control of the sound VSC converters, switching on the controllable energy dissipation devices at the receiving end and retarding of the LCC converters at the sending end, adjusting the DC power of the converters at the sending and receiving ends, are adaptively coordinated within converters, between converters and between stations to effectively mitigate the overvoltage issues in VSC sub-modules and realize AC fault ride-through of the hybrid cascaded UHVDC system. A closed-loop real-time digital simulation test platform is built based on actual control and protection devices and the topology used on site. The test results show the validity of the proposed strategy. The proposed strategy has been successfully applied in the Baihetan-Jiangsu hybrid UHVDC project.